Effects of once-daily extended release quetiapine fumarate on patient-reported outcomes in patients with generalized anxiety disorder - Endicott J (Dove Medical Press, 2012)
Jean Endicott,1 Henrik Svedsäter,2 Julie C Locklear21Department of Psychiatry, Columbia University, New York, NY; 2AstraZeneca Pharmaceuticals, Wilmington, DE, USABackground: We evaluated the effects of once-daily extended-release quetiapine fumarate (quetiapine XR) on patient-reported outcomes in generalized anxiety disorder (GAD).Methods: This is a report of a pooled analysis from three acute 8-week, randomized, placebo-controlled, fixed-dose (50, 150, 300 mg/day) studies and a 52-week maintenance flexible dose (50–300 mg/day) study of quetiapine XR monotherapy in patients with GAD. Quality of Life Enjoyment and Satisfaction Questionnaire Short Form (Q-LES-Q-SF) percent maximum total scores (items 1–14), item 15 ("satisfaction with medication"), item 16 ("overall life satisfaction"), and Pittsburgh Sleep Quality Index (PSQI) global scores are reported. Sheehan Disability Scale (SDS) total scores were also assessed (maintenance study only).Results: The acute studies showed significant improvements at week 8 in Q-LES-Q-SF percent maximum total score with quetiapine XR 150 mg/day (P < 0.001) and item 16 with quetiapine XR 50 (P < 0.05) and 150 mg/day (P < 0.001) versus placebo; PSQI global scores significantly improved with quetiapine XR 50, 150, and 300 mg/day versus placebo (P < 0.001). The maintenance study showed significant benefits versus placebo with quetiapine XR 50–300 mg/day in Q-LES-Q-SF percent total score, item 15 and item 16 scores, PSQI global score, and SDS total score.Conclusion: Quetiapine XR 150 mg/day (acute studies) and 50–300 mg/day (maintenance study) improved quality of life, overall functioning, and sleep quality in patients with GAD.Keywords: atypical antipsychotic, anxiety disorders, quality of life, sleep quality, functioning, randomized studies